Alpha-Synuclein, Oxidative Stress and Autophagy Failure: Dangerous Liaisons in Dopaminergic Neurodegeneration - Stefanoni, Giovanni; Sala, Gessica; Tremolizzo, Lucio; Brighina, Laura; Ferrarese, Carlo (IntechOpen, 2011)
None